2003
DOI: 10.1080/07924259.2003.9652563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytochalasin B on fertilization and ploidy in the Pacific oysterCrassostrea gigas

Abstract: The effects of cytochalasin B on fertilization and ploidy in Crassostrea gigas were examined in a controlled experiment. This enabled us to better understand why variable ploidy results have been found with the retention ofpolar bodies in previous studies on bivalve mollusks, and what the interaction with fertilization may be. By looking at the early development of Crassas/rea gigas embryos with sequential sampies stained using Hoechst 33258, a fluorescent DNA-specific dye, we compared normal evolution of fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Nonpenetration may be a side effect of CB (Longo, 1978;Ledu and McCombie, 2003). We have also observed unusual patterns of PB expulsion in other ploidy manipulation experiments; on rare occasions these included the expulsion of most or all the genetic material in one PB (Ledu and McCombie, 2003). The effects of CB may therefore be diverse.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Nonpenetration may be a side effect of CB (Longo, 1978;Ledu and McCombie, 2003). We have also observed unusual patterns of PB expulsion in other ploidy manipulation experiments; on rare occasions these included the expulsion of most or all the genetic material in one PB (Ledu and McCombie, 2003). The effects of CB may therefore be diverse.…”
Section: Discussionmentioning
confidence: 59%
“…The objective was to determine whether or not the paternal parents had participated in the cross, first because our initial ploidy results had revealed diploids in batch 3, and it is known that diploid gynogens may be produced by CB treatments in this species (Guo et al, 1993). Second, results from our embryogenesis study had also indicated some double polar body retention, which could lead to tetraploid gynogens (Guo et al, 1993;Ledu and McCombie, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…This principal has formed the basis of ploidy manipulation in many aquatic organisms with external meiosis. Results in oyster embryos also indicate a role of CB in the sperm–egg relationship that can lead to tetraploidy through gynogenesis (Ledu & McCombie 2003). The present study therefore used early treatments to potentially exploit this mechanism.…”
mentioning
confidence: 91%
“…Guo & Allen 1994). If there was no paternal contribution, then the gynogenetic hypothesis of Ledu and McCombie (2003) would be confirmed.…”
mentioning
confidence: 99%
“…The survival rate of larvae under all three methods in this study decreased signi during the rst 10 days under all three methods. could be rstly due to the very high toxicity of the inducer, which severely deteriorated the larval survival rate (Ledu and McCombie 2003;Yang et al 2000; Peachey and Allen 2016). Additionally, blocking PB1 has been known to induce aberrations in chromosome segregation, such as tripolar segregation and heterogeneous chromosome distribution, causing massive aneuploidy and reduced viability (Guo et al 1992a).…”
Section: The Tetraploid Rate Was Signi Cantly Affected With the Induc...mentioning
confidence: 99%